The Abode of the Other (Museums in German Concentration Camps 1933-1945) - Božidar Jezernik (Journal of Ethnology and Folkloristics)
In major German concentration camps, museums were set up with the aim of collecting exhibits and displaying them within a Rassenkunde (race science) framework. As the discourse of racial anthropology was built on the rhetoric of the difference between the ‘pure’ races and people with ‘inferior hereditary quality,’ SS museums put on display ‘pieces of evidence’ with a view to rendering present and visible that which was absent and invisible: the hierarchical order of different races. Thus, collections displayed in SS museums in concentration camps were instrumental in the process of defining the Aryan Übermensch (superhuman) as the personification of all desirable physical, cultural and intellectual attributes, born to conquer and rule the world as a member of the Herrenvolk (master race), and the non-Aryan, above all the Jewish Untermensch (subhuman) as his opposite, a radically other and barely human, suitable only for menial chores.The first museum established in German concentration camps was opened in Dachau early in the 1930s. Similar museums worked in other German concentration camps (Buchenwald, Mauthausen and Auschwitz). The richest was the museum in Gusen I, the sub-camp of Mauthausen. In autumn 1940, when the SS began with the construction of a railway between KZ Gusen I and St Georgen railway station, a grave-yard from the Bronze-Age was found. All the finds were housed in an archaeological museum that was established at the Museumsbaracke (museum barrack) within the camp. By the side of archaeological findings, human skins, skulls and body parts were put on view. At the time of the liberation of Gusen I, on 5 May 1945, a collection of 286 body parts was found and a voluminous album with fragements of tattooed human skin. Today, from all the SS museums’ anthropological exhibits not a single one is on display in the museum exhibitions set up in the former concentration camps. So far, these establishments also escaped the attention of scholarly research. Thus, when I interviewed historians employed in Mauthausen Memorial Museum and in Gusen Visitors’ Centre, in 2005, they were completely unaware of the existence of above-mentioned museums during the war time.